Psychological interventions to create child-friendly school in senior high schools levels in Indonesia - Suratno Suratno; Wantini Wantini; Suyatno Suyatno (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
School violence, including bullying, is one of the severe problems faced by educational institutions in Indonesia.  Bullied students are more likely to suffer anxiety, unhappiness, and uncomfortable feelings. As a result, they are unable to perform well in their school activities which affect their learning outcome. This study aims to find suitable types and models of psychological intervention to solve the school violence problem. Specifically, this psychological intervention is expected to help create a child-friendly school in Indonesia at the senior high school level. this study applies the Systematic Literature Review (SLR) method by operating the academic search engine, namely “Google Scholar” and “Research Gate.”  The result shows there are 22 articles on psychological intervention. Regarding types, two types of psychological intervention can be applied to creating a child-friendly school at the senior high school level in Indonesia: social intervention and group counseling intervention using the Tazkitatun-nafsi self-management technique. Besides there are four models of intervention approaches, namely psychoeducational model intervention; b) intervention with a behavioral model; c) intervention with a neuropsychological model; and d) intervention with the cognitive model.